Bibliotecas universitárias na EAD: processos e trajetórias em discussão - Moema Brandao da Silva (2014)
The research objective is to seize and analyze the elements of institutional policy, the technological infrastructure and existing human resources in university libraries systems of Federal Universities that offer distance undergraduate courses, through the Open University of Brazil (UAB), and check which elements interfere and limit the role of the librarian in distance education mode. Theoretically the work was caused by the discussion referring to the importance of the library at the University, as well as in distance education mode (EAD), to try and identify the fundamental aspects to understanding University libraries roles in distance education. The methodology used was to combine the elements of quantitative and qualitative research; the first step consisted of exploratory research using information available on the website of CAPES to identify the Federal Universities accredited by the MEC that offer undergraduate courses in distance mode. The instruments used to collect data were questionnaires and interviews. From a total of 50 active Federal Universities in distance education, 23 returned to questions sent by e-mail; among these 18 reported not act strictly in that mode and 5 showed different actions within the distance education. With the results of the exploratory phase we chose to work with 5 University Libraries of Federal Universities: UFMG, UFOP, UnB, UFSC and UFMT. In the second stage 5 library directors, 5 distance education directors and 1 distance education librarian involved with distance education and a member of staff of one of the universities surveyed were interviewed. The research result showed that institutional policy for distance mode is under construction and the directions in respect of the shares for the participation of the university library in this context are incipient. If this also, that technological and human resource structure using the same existing infrastructure in the University attendance. It is noteworthy that the distance education in its breadth is voluntary and the lack of labor relations do not contribute to the creation of bonds. Identified the contradictory elements that do not potentiate the activity of the library/ librarian in distance education, have to be related to the following factors: pedagogical, political, operational, strategic and cultural. The results indicate the importance of achieving greater dialogue between university libraries and the centers in charge of distance education, as well as the relevance of incorporate EAD under university policy, allowing the guarantee the right and the access to information to the undergraduate in the distance education mode.